Table-top nanoscale coherent imaging with XUV light - Rothhardt, Jan; Tadesse, Getnet K.; Eschen, Wilhelm; Limpert, Jens (Journal of Optics, 2018)
Modern laser-based XUV light sources provide very high photon fluxes which have previously only been available at large scale facilities. This allows high-performance XUV nanoscale imaging to be implemented in a table-top manner, and thus qualifies XUV imaging as a novel imaging technique complementing electron and visible-light microscopy. This article presents the current state-of-the-art in table-top XUV light sources and matched coherent imaging schemes. Selected experiments demonstrate the unique capabilities of XUV imaging - namely, nanoscale (sub-20 nm) resolution, single shot imaging, imaging of extended samples and 3D imaging of μm-sized objects. In addition, future prospects will be discussed, including scaling to few-nm resolution, extension to the soft x-ray spectral region, chemically-specific imaging at absorption edges and time-resolved imaging on femtosecond time-scales.
CRIS-Team Scopus Importer:2023-04-20
Keywords: coherent diffractive imaging; high harmonic generation; nanoscale imaging; ultrafast imaging; x-ray lasers; XUV light